Differences among western European countries in anticoagulation management of atrial fibrillation - Le Heuzey, Jean-Yves; Ammentorp, Bettina; Darius, Harald; De Caterina, Raffaele; Schilling, Richard John; Schmitt, Josef; Zamorano, José Luis; Kirchhof, Paulus (Thrombosis and Haemostasis, 2014)
Due to improved implementation of guidelines, new scoring approaches to improve risk categorisation, and introduction of novel oral anticoagulants, medical management of patients with atrial fibrillation (AF) is continuously improving. The PREFER in AF registry enrolled 7,243 consecutive patients with ECG-confirmed AF in seven European countries in 2012–2013 (mean age: 71.5 ± 10.7 years; 60.1% males; mean CHA2DS2-VASc score: 3.4). While patient characteristics were generally homogeneous across countries, anticoagulation management showed important differences: the proportion of patients taking vitamin K antagonists (VKAs) varied between 86.0% (in France) and 71.4% (in Italy). Warfarin was used predominantly in the UK and Italy (74.9% and 62.0%, respectively), phenprocoumon in Germany (74.1%), acenocoumarol in Spain (67.3%), and fluindione in France (61.8 %). The major sites for international normalised ratio (INR) measurements were biology laboratories in France anticoagulation clinics in Italy, Spain, and the UK, and physicians’ offices or self-measurement in Germany. Temporary VKA discontinuation and bridging with other anticoagulants was frequent (at least once in the previous 12 months for 22.9% of the patients, on average; ranging from 29.7% in Germany to 14.9% in the UK). Time in therapeutic range (TTR), defined as at least two of the last three available INR values between 2.0–3.0 prior to enrolment, ranged from 70.3% in Spain to 81.4% in Germany. TTR was constantly overestimated by physicians. While the type and half-lives of VKA as well as the mode of INR surveillance differed, overall quality of anticoagulation management by TTR was relatively homogenous in AF patients across countries.
Keywords: Registry; cross-sectional; anticoagulation; vitamin K antagonists; anticoagulation quality; INR